Abundance and diversity of nitrogen-removing microorganisms in the UASB-anammox reactor - Chen, Rui (PLoS One, 2019)
Anaerobic ammonium oxidation is considered to be the most economical and low-energy biological nitrogen removal process. So far, anammox bacteria have not yet been purified from cultures. Some nitrogen-removing microorganisms cooperate to perform the anammox process. The objective of this research was to analyze the abundance and diversity of nitrogen-removing microorganisms in an anammox reactor started up with bulking sludge at room temperature. In this study, the ammonia-oxidizing archaea phylum Crenarchaeota was enriched from 9.2 to 53.0%. Nitrosomonas, Nitrosococcus, and Nitrosospira, which are ammonia-oxidizing bacteria, increased from 3.2, 1.7, and 0.1% to 12.8, 20.4, and 3.3%, respectively. Ca. Brocadia, Ca. Kuenenia, and Ca. Scalindua, which are anammox bacteria, were detected in the seeding sludge, accounting for 77.1, 11.5, and 10.6%. After cultivation, the dominant genus changed to Ca. Kuenenia, accounting for 82.0%. Nitrospirae, nitrite oxidation bacteria, decreased from 2.2 to 0.1%, while denitrifying genera decreased from 12.9 to 2.1%. The results of this study contribute to the understanding of nitrogen-removing microorganisms in an anammox reactor, thereby facilitating the improvement of such reactors. However, the physiological and metabolic functions of the ammonia-oxidizing archaea community in the anammox reactor need to be investigated in further studies.